Shock wave-boundary-layer interactions - Babinsky, Holger; Harvey, John (Cambridge University Press, 2011)
"This is the first book devoted solely to the phenomenon of Shock Wave Boundary Layer Interactions and covers all flow regimes where SBLI's occur"--Provided by publisher
Keywords: Shock waves.; Boundary layer.; elektronické knihy; electronic books